Hashtag dan Kata Kunci di Media Sosial Seputar Fenomena Citayam Fashion Week - Yohana, Yohana; Paramita, Sinta (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
Social media online communities are built because of similarities and connectedness. This is also the case with the social phenomenon Citayam Fashion Week, which is popular in Jakarta in 2022. Researchers are interested in the digital communication and virtual opinions that occur through hashtags and keywords in a social phenomenon. The researcher used a qualitative approach with the netnography method. Statistical data was obtained through analyse.io and screenshots of video content on TikTok social media. The results showed that the spread of information about a phenomenon was fast and comprehensive due to the participation of social media users. Communication-related to Citayam Fashion Week involves users as communicators and communicants through open spaces of expression and participation in the TikTok application. The role of hashtags and keywords here also enhances the communication activities to reach a wider audience. Komunitas online media sosial dibangun karena adanya kesamaan dan keterhubungan. Hal ini terjadi pula pada fenomena sosial, Citayam Fashion Week, yang popular di Jakarta pada tahun 2022. Peneliti tertarik untuk mengetahui komunikasi digital dan opini virtual yang terjadi melalui hashtag dan kata kunci dalam sebuah fenomena sosial. Peneliti menggunakan pendekatan kualitatif dengan metode netnografi. Data statistik diperoleh melalui analisa.io dan tangkapan layar konten video di media sosial TikTok. Hasil penelitian menunjukkan bahwa penyebaran informasi mengenai suatu fenomena begitu cepat dan luas karena partisipasi pengguna media sosial. Komunikasi terkait Citayem Fashion Week berlangsung dengan melibatkan pengguna sebagai komunikator maupun komunikan melalui ruang berekspresi dan partisipasi yang terbuka pada aplikasi TikTok. Peran hashtag dan kata kunci disini turut menyempurnakan kegiatan komunikasi yang berlangsung untuk menjangkau audiens yang lebih luas.